A Rare Case of a Renal Cell Carcinoma Confined to the Isthmus of a Horseshoe Kidney. (22nd June 2015) - Kongnyuy, Michael; Martinez, Daniel; Park, Anthony; McCormick, Barrett; Parker, Justin; Hall, Mary
Abstract : Horseshoe kidney (HSK) is the most common renal anomaly. Reports of the incidence of renal cell carcinoma (RCC) in HSK are conflicting. Very few cases of isthmus-located RCC have been reported in the literature. We report a unique case of an isthmus-located RCC. Proper vascular and tumor imaging prior to surgery is key to successful tumor removal.